Waste Management In Kepulauan Seribu: Identifying Key Factors And Enhancing Business Processes - Saptomo, Endro; Nurmala, Nurmala (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
Business process in waste management play an important role in influencing the effectiveness of household waste management in archipelago area like Kepulauan Seribu. Kepulauan Seribu is one of the areas that has potential in the tourism sector. Despite its unique location as an archipelago, Kepulauan Seribu experiences difficulties managing its waste and must transport it to landfills in Jakarta. The aims of this research are to develop the business process of household waste management program, identify the inhibiting and driving factors of the household waste management program and provide the suggestions for improving business process in Kepulauan Seribu. This research is based on qualitative methods. In-depth interviews with targeted respondents are used for data collection. Business process analysis such as waste analysis, value-added analysis, why-why analysis and pareto analysis are employed to further enhance the understanding of waste management processes and identify areas for improvement. This research discovered that business process in waste management in Kepulauan Seribu required to be improved and eliminate the unnecessary processes. Additionally, this study helps Kepulauan Seribu's household waste management program, and it is anticipated that it will help the local government formulate more sensible and useful policies.